2015
DOI: 10.1002/jts.22011
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Scores on a Screening Instrument for PTSD Among World Trade Center Rescue, Recovery, and Clean‐Up Workers

Abstract: The longitudinal course of posttraumatic stress disorder (PTSD) over 8-9 years was examined among 16,488 rescue and recovery workers who responded to the events of September 11, 2001 (9/11) at the World Trade Center (WTC; New York, NY), and were enrolled in the World Trade Center Health Registry. Latent class growth analysis identified 5 groups of rescue and recovery workers with similar score trajectories at 3 administrations of the PTSD Checklist (PCL): low-stable (53.3%), moderate- stable (28.7%), moderate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 30 publications
(32 reference statements)
3
59
0
Order By: Relevance
“…The four trajectories identified in WTC tower survivors are similar to those found in WTC police responders and the general population, which demonstrates that similar posttraumatic responses are found across populations of first responders and civilians (Feder et al., ; Galatzer‐Levy et al., ; Pietrzak, Feder, Singh et al., ). When considering other WTC cohorts, fewer tower survivors from the current study were identified as having stable low symptoms and more were identified as having chronically elevated PTSS (10.4%) than in samples of police responders (4.4–5.3%; Feder et al., ; Pietrzak, Feder, Singh et al., ); New York area residents and workers (8.0%; Welch et al., ); and rescue, recovery, and clean‐up workers (4.0%; Maslow et al., ). The disparate findings are likely dependent on several factors but may be due in part to the proximity and number of unique exposures experienced by WTC tower survivors who received little or no prior training or mental preparedness to deal with such events.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The four trajectories identified in WTC tower survivors are similar to those found in WTC police responders and the general population, which demonstrates that similar posttraumatic responses are found across populations of first responders and civilians (Feder et al., ; Galatzer‐Levy et al., ; Pietrzak, Feder, Singh et al., ). When considering other WTC cohorts, fewer tower survivors from the current study were identified as having stable low symptoms and more were identified as having chronically elevated PTSS (10.4%) than in samples of police responders (4.4–5.3%; Feder et al., ; Pietrzak, Feder, Singh et al., ); New York area residents and workers (8.0%; Welch et al., ); and rescue, recovery, and clean‐up workers (4.0%; Maslow et al., ). The disparate findings are likely dependent on several factors but may be due in part to the proximity and number of unique exposures experienced by WTC tower survivors who received little or no prior training or mental preparedness to deal with such events.…”
Section: Discussionmentioning
confidence: 74%
“…Studies of WTC first responders, rescue and recovery workers, and New York metropolitan–area residents have identified between four and six PTSS trajectories (Feder et al., ; Maslow et al., ; Pietrzak, Feder, Singh et al., ; Welch et al., ). Similar to findings related to WTC survivors, other studies of PTSS in various populations and in response to numerous types of traumas have typically found four trajectories: low symptom, recovering, worsening, and chronically elevated (see Bonanno & Mancini, ; Galatzer‐Levy, Huang, & Bonanno, ).…”
mentioning
confidence: 99%
“…The stress sensitization hypothesis suggests that prior trauma exposure could increase vulnerability to subsequent stressors or traumas. Several studies of disaster populations indeed found evidence that secondary disaster stressors (Kessler et al., ; Yabe et al., ) and postdisaster life events and adversities (Maes, Mylle, Delmeire, & Janca, ; Maslow et al., ; Shrira, Palgi, Ben‐Ezra, & Shmorkin, ; Smid et al., ; Zvolensky et al., ) were associated with increased psychopathology. However, only a few studies specifically examined the psychological effects of two community‐wide disasters on the same population.…”
mentioning
confidence: 99%
“…Several studies of WTC responders have reported persistently high rates of posttraumatic stress and depressive symptoms, and chronic Diagnostic and Statistical Manual of Mental Disorders (4th ed., text rev. ; DSM‐IV‐TR ; American Psychiatric Association, ) posttraumatic stress disorder (PTSD) since September 11, 2001 (e.g., Bromet et al., ; Cone et al., ; Liu, Tarigan, Bromet, & Kim, ; Luft et al., ; Maslow et al., ; Wisnivesky et al., ). Hurricane Sandy thus provided a unique opportunity to examine the mental health impact of a second disaster in a high‐risk cohort.…”
mentioning
confidence: 99%
“…We now understand that postdisaster mental health issues in adults and children were common and, importantly, also often chronic, including symptoms of posttraumatic stress disorder, anxiety, and depression related not only to the immediate trauma, but also to the longerterm recovery and rebuilding efforts and medical illnesses (16,(37)(38)(39)(40)(41)(42)(43). Comorbidity of mental and physical health issues compounds complexity of diagnosis and management.…”
Section: Special Article What We Have Learned About Health Effectsmentioning
confidence: 99%